2004
DOI: 10.1002/jsfa.1885
|View full text |Cite
|
Sign up to set email alerts
|

Flavonoid glycosides and antioxidant capacity of various blackberry, blueberry and red grape genotypes determined by high‐performance liquid chromatography/mass spectrometry

Abstract: Anthocyanin and flavonol glycosides of various blackberry, blueberry and red wine grape genotypes were identified and measured by a high-performance liquid chromatographic (HPLC) separation method with photodiode array (PDA) and mass spectrometric (MS) detection. With this method, two distinct elution regions of anthocyanins and flavonols were obtained with near baseline separation of most compounds. Blackberry, blueberry and red wine grape genotypes varied markedly in total anthocyanins and total flavonols as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

44
257
12
4

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 340 publications
(330 citation statements)
references
References 35 publications
44
257
12
4
Order By: Relevance
“…The highest TPH was found in BS and the lowest in CT and NV. Clark et al (2002) and Cho et al (2005) found that LN had higher amount of total phenolics than NV, which confirmed our results. Very high variations and discrepancy among cultivars and between years were observed by other authors (Sellappan et al 2002, Reyes-Carmona et al 2005).…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…The highest TPH was found in BS and the lowest in CT and NV. Clark et al (2002) and Cho et al (2005) found that LN had higher amount of total phenolics than NV, which confirmed our results. Very high variations and discrepancy among cultivars and between years were observed by other authors (Sellappan et al 2002, Reyes-Carmona et al 2005).…”
Section: Resultssupporting
confidence: 89%
“…An important lower or higher variability was reported previously (Sellappan et al 2002). The different TFC reported when compared to previous studies may be due to maturity at harvest and cultivar difference (Cho et al 2005, Reyes-Carmona et al 2005.…”
Section: Resultscontrasting
confidence: 58%
“…Nevertheless, they are within the concentrations described by Cho, Howard, Prior, and Clarck (2003) in different varieties of red grapes and by Lee and Talcott, (2004) in Muscadina grapes.…”
Section: Flavonolssupporting
confidence: 72%
“…In the year 2003, significant differences were observed between both types of grapes (p ¼ 0.035) at confidence level of 95%, in which the average concentration of anthocyanins reached up to 682.27 + 14.82 mg/kg in conventional grapes and 821.37 + 31.14 mg/kg in organic grapes ( Ferna´ndez et al, (2003) and in different varieties of red wine grapes by Cho, Howard, Prior, and Clarck (2003). These concentrations were also similar to those obtained by Valls, Lampreave, Nadal, and Arola (2000) in Tempranillo and Cabernet Sauvignon varieties and lower than those reported in Monastrell grapes by Cantos et al, (2003).…”
Section: Anthocyaninsmentioning
confidence: 96%
“…On the contrary, peonidin is found in red-purplish fruits at lower pH conditions [23]. Petanin (petunidin-3-[6-O-(4-O-E-p-coumaroyl-O-α-l-rhamnopyranosyl)-β-d-glucopyranoside]-5-O-β-d-glucopyranoside), is also one of the acylated anthocyanins which are stable at higher pH [18].…”
Section: Color and Stability Of Anthocyanin Pigmentsmentioning
confidence: 99%